Correlation of IL-10 Levels with the Bacterial Index in Multibacillary Leprosy - Fitriyanti, Fitriyanti; Lipinwati, Lipinwati; Istarini, Attiya; Ekaputri, Tia Wida (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2025)
Background: Multibacillary (MB) leprosy features high bacillary load and an immunoregulatory milieu. Methods: A comparative cross-sectional study enrolled 70 participants (MB = 35; controls = 35). Categorical variables were compared with Chi-square/Fisher’s exact tests; medians with Mann–Whitney U. Spearman’s rank correlations were computed within groups. Results: Age did not differ (p = 0.458 and p = 1.000), whereas occupation and education did (p = 0.038 and p = 0.029). The Bacterial Index (BI) was markedly higher in MB (median 3 [IQR 4]) than controls (0 [0]; p < 0.001). IL-10 levels were higher in MB (1.97 [4.30] pg/mL) versus controls (1.12 [1.96] pg/mL; p = 0.033). In MB, BI correlated positively with IL-10 (ρ = 0.357; p = 0.035). Conclusions: MB patients exhibit substantially higher bacillary burden and elevated IL-10 relative to controls. The positive BI–IL-10 association in MB supports a tolerogenic immune profile linked to bacterial load, while PGE₂ showed limited discriminatory value in this sample. Larger, adjusted studies are warranted to validate these relationships and explore their clinical utility.